1986
DOI: 10.1002/1098-108x(198602)5:2<347::aid-eat2260050213>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Total body potassium, intracellular potassium and body composition in patients with anorexia nervosa during refeeding

Abstract: The total body potassium content and the potassium concentration in serum and erythrocytes was measured in 16 patient with anorexia nervosa (8 “vomiters” and 8 “restricters”). The data were compared with results obtained for 11 normal controls, whose body weight was 99.6% ± 4.99% of ideal body weight (IBW). Patients were studied before treatment (IBW 72.8 ± 6.3%) and after an average weight gain of 19%. Serum potassium was not significantly different between groups, but potassium concentration was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Similarly, during the treatment of malnourished children weight gain was more rapid in the early recovery, with a tendency to lay down more fat in following phases (Standard et al, 1959). As far as refed anorectic patients are concerned, cross-sectional and longitudinal studies have given fairly contradictory results, indicating that FM represents, on average, 21 -77% of the weight regained (Russel & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001). This discrepancy could be explained by differences in baseline patients' general characteristics, measurement meth- Body composition changes in anorexia L Scalfi et al ods, refeeding programmes, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, during the treatment of malnourished children weight gain was more rapid in the early recovery, with a tendency to lay down more fat in following phases (Standard et al, 1959). As far as refed anorectic patients are concerned, cross-sectional and longitudinal studies have given fairly contradictory results, indicating that FM represents, on average, 21 -77% of the weight regained (Russel & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001). This discrepancy could be explained by differences in baseline patients' general characteristics, measurement meth- Body composition changes in anorexia L Scalfi et al ods, refeeding programmes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery. The studies available in the literature also indicate that FM represents 21 -77% of the weight gained (Russell & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001;Grinspoon et al, 2001), while the number of calories needed to put down body mass seems to increase during refeeding (Salisbury et al, 1995). Nevertheless, despite the widespread use of anthropometric techniques for the assessment of nutritional status, only a few studies have so far examined the changes in skinfolds and circumferences which occur during weight recovery (Forbes et al, 1984;Nuñez et al, 1994;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The published studies on body composition in eating disorders are difficult to compare and mostly based on very small groups. We have found only a few studies (Pirke et al 1986;Charest-Lilly et al 1987;Mayo-Smith et al 1989;Hannan et al 1990Hannan et al , 1993aVaisman et al 1991;Russell et al 1994;Young et al 1994) in which more than fifteen patients have been investigated.…”
mentioning
confidence: 99%
“…Seven patients with anorexia nervosa, 10 patients with bulimia, and 14 healthy controls were studied by the potassium 40 method as described in detail by Pirke et al (1986) and by the electrical conductivity method. Clinical data are given in Table 1.…”
Section: Patients and Control Subjectsmentioning
confidence: 99%
“…However, the correlation between results obtained by the potassium 40 method and the conductivity method were not as high as reported by Lukaski et al (1985) for healthy men. A reason for this may be that the correction for intracellular potassium loss by measuring potassium content in erythrocytes is not sufficiently precise for use in patients with eating disorders (Pirke et al, 1986). Furthermore, water and electrolyte disturbances are frequently observed in anorexic patients (Gold et al, 1983) and may introduce minor changes in conductance and resistance, so that the formula applied to calculate fat-free mass may not be completely appropriate for emaciated subjects.…”
Section: Disc Usslo Nmentioning
confidence: 99%